Caracterización socio-económica de las unidades productoras de maíz suave (Zea mays L.) en la parroquia Santa Fé, Guaranda provincia Bolívar - Garcés Rivera, Cristhian Roberto (2020)
Corn is an agricultural product that is produced the most in the world, due to its nutritional qualities for the production of animal protein, human consumption and industrial use, it has become one of the most important products in international markets. In Ecuador, around 187,521 hectares of corn are grown annually, covering 54,858 Agricultural Production Units UPAs, with an average yield of 2.6 t / ha. In the Santa Fe parish, agricultural activity constitutes an important part of the income of the economically active population. Corn cultivation involves a series of steps necessary to achieve its harvest. From the sowing and subsequent harvest, to the sale to intermediaries or distributors, corn requires plowing techniques, the quality of the seed or the frequency of application of fertilizers, fungicides and herbicides, can cause a problem in the efficiency of the production processes The proposed objectives were: i) Identify the agricultural production units that are dedicated to the cultivation of soft corn in the Santa Fe parish. ii) Carry out the georeferencing and socio-productive and economic characterization of the soft corn production systems. iii) Define the technological package used in the cultivation of soft corn (Zea mays. l), and socialization of the results. The methodology of the survey, rapid rural diagnosis and the interview with a pre-established questionnaire, with open and closed questions, the sample was made up of the universe and the analysis was used Descriptive Statistics with the Excel program; Among the main results is that 67% are carried out by men and 33% by women, which shows that the man is the one who directs the UPAs. In the study area, most of the soils are owned by their own, 48% and 29% are leased land for the cultivation of soft corn, and 23% belong to people who own land, but also rent. The producers use seed improved with 77% the Guagal 111 variety due to its adaptation to the climatic conditions of the sector, the products do not use the same technological package is very varied, which are mostly recommended by the owners of the shops of agricultural inputs, there are around 606 maize production units with an average of 0.37 hectares with a mapped area of 224.5679